Activité de l’enseignant et dynamique coopérative au sein de dyades d’élèves. Une étude de cas dans des tâches d’escalade en Education Physique - Agathe Evin; Carole Sève; Jacques Saury (Recherches en Éducation)
This study analyzed how the teacher’s interventions influence cooperation between students in dyads in climbing. It was especially aimed to identify and characterize (a) the typical situations where the teacher’s activity was meaningful for one and/or the two students in the dyad, and (b) the effects of the teacher’s activity on the students’ cooperative activity. This study was carried out referring to the “course of action” theoretical and methodological framework (Theureau, 2006). The results showed five typical situations in which the teacher’s activity was meaningful for the students and two kinds of effects of the teacher’s activity on cooperation: “positive effects”, facilitation of cooperation between students thanks to development of their trust in the skills and the reliability of their partner’s activity, and “negative effects”, harmful to the cooperation. These effects are interpreted in relation to two influence processes respectively qualified ‘validation process” and “invalidation process’ of students’ action by the teacher.